Antimicrobial efficacy of three medicinal plants Glycyrrhiza glabra, Ficus religiosa, and Plantago major on inhibiting primary plaque colonizers and periodontal pathogens: An in vitro study - Hunny Sharma; G Y Yunus; Ashok Kumar Mohapatra; Reena Kulshrestha; Rohit Agrawal; Monika Kalra (Wolters Kluwer Medknow Publications, 2016)
Introduction: From ancient times, plants with medicinal values are being tested and used in treatment of various infectious disease. Aims and Objectives: The presentin vitro study was designed to assess the antimicrobial activity of three commonly available medicinal plants Glycyrrhiza glabra, Ficus religiosa, and Plantago major on inhibiting Primary plaque colonizers and periodontal pathogens. Materials and Methods: Bark of G. glabra, Stem of F. religiosa, and husk of P. major were collected, crushed into fine powder, and dissolved in 67% ethanol. Extracts were then subjected to test antimicrobial efficacy against primary plaque colonizers and periodontal pathogens using Kirby-Bauer disc diffusion method. Mean zone of inhibition (ZOI) was measured by HI antibiotic zone scale. One-way ANOVA using Tukey's post hoc and t-test were applied for statistical analysis. Results: G. glabra was found to have potential antibacterial activity against primary plaque colonizers and periodontal pathogens with highest mean ZOI measuring 9.2 ± 1.09 mm and 10.6 ± 0.54 mm at 24 h, respectively. F. religiosa showed antibacterial activity against primary plaque colonizers only at 48 h with mean ZOI of 2.6 ± 0.54 mm. P. major showed no antibacterial activity against any of the microorganism in this study. Tukey's post hoc test showed statistically nonsignificant difference between G. glabra and standard antibiotic (vancomycin 10 mcg) for periodontal pathogens. Conclusion:G. glabra and F. religiosa showed antibacterial activity against primary plaque colonizers and periodontal pathogens. However, further studies should be undertaken to affirm the same and test their efficacy in different concentration and clinical utility.